Manajemen Pariwisata Berbasis Lingkungan di Buleleng, Bali: Strategi, Tantangan, dan Integrasi Kearifan Lokal - Putu Ayu Sita Laksmi; Bayu Pasupati (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2025)
Buleleng Regency in North Bali emerges as an alternative destination offering a different tourism paradigm from the crowded southern areas of Bali. This article aims to analyze the implementation of environment-based tourism management in Buleleng, focusing on the strategies, challenges, and the role of the local wisdom of Tri Hita Karana. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with key stakeholders, field observations at primary tourist locations, and a review of policy documents. The research findings indicate that Buleleng possesses great natural and cultural potential as a foundation for sustainable tourism. The implementation of environment-based tourism management is realized through various initiatives, including the development of strong Community-Based Tourism (CBT), waste management policies, biodiversity conservation, and the promotion of special interest tourism. The philosophy of Tri Hita Karana serves as an operational guide in creating harmony between tourism activities, environmental sustainability, and the socio-cultural life of the community. However, this implementation faces complex challenges, such as infrastructure development pressure, fluctuations in tourist numbers, budget limitations, and conflicts of interest among stakeholders. This article concludes that the long-term success of Buleleng's tourism heavily depends on the consistency of a collective commitment to prioritize a sustainable approach, strengthen the capacity of the local community, and make local wisdom the core of every decision-making process. The implications of this research provide valuable lessons for similar destinations striving to balance economic growth with ecological and cultural sustainability.